(3GdcJjHI GdcGefI ajef dbjfGg HGdCfOdS ef TYQGA GdeGFI GdKGefIs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdCOH ai LejY eG ddafhf ef GdCShGb s
(3BNQgG (B:s
(3Edi gfG JhLO gPg GdcJjHI , hdYd eDdagG NQeJg GdefjI bHd JeGegG hGddg CYde s
(3BNQgG agQS CSeGA GdTYQGA hGdeJQLejf ai GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B337 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B121 s
Keywords: (3GdJGQjNs